Is the brain involved in patients with late‐onset Pompe disease?. Issue 3 (25th January 2022) - van den Dorpel, Jan J. A.; van der Vlugt, Willemijn M. C.; Dremmen, Marjolein H. G.; Muetzel, Ryan; van den Berg, Esther; Hest, Roos; de Kriek, Joni; Brusse, Esther; van Doorn, Pieter A.; van der Ploeg, Ans T.; van den Hout, Johanna M. P.; van der Beek, Nadine A. M. E.
Abstract: Our objective was to investigate brain structure, cerebral vasculature, and cognitive function in a cohort of patients with late‐onset Pompe disease, with particular reference to the differences from those with the classic infantile phenotype, where extensive white‐matter abnormalities (WMA) and impaired cognition on long‐term enzyme treatment are reported in a subset of patients. Brain imaging (T1, T2, T2 fluid‐attenuated inversion recovery, susceptibility‐weighted images, and magnetic resonance angiography–time of flight) was combined with extensive cognitive testing of general intelligence (Wechsler IQ Test, Montreal Cognitive Assessment [MoCA]) and specific neuropsychological domains (verbal fluency, cognitive flexibility, attention, memory, and visuospatial abilities). We included 19 patients with late‐onset Pompe disease (age range 11‐56 years). Two patients showed mild punctate WMA within normal range for age, with a Fazekas score (FS) of 1 to 2. Magnetic resonance angiography revealed a slight vertebrobasilar dolichoectasia in two patients yet did not show any aneurysms or vascular dissections. Most patients had age‐adjusted scores within the normal range for the Wechsler index scores (verbal comprehension, perceptual reasoning, working memory, and processing speed) and combined total intelligence (IQ) score (median 101, interquartile range 91‐111; one patient had a below‐average score for total IQ) as well as for the specific domains verbal fluency, attention, and memory. A subset of patients performed suboptimally on the Rey Complex Figure Test (9/14 patients) or cube‐copying/clock‐drawing test of the MoCA (8/10 patients). We therefore concluded that our study showed no brain abnormalities, other than minor microvascular lesions considered within normal range for age, nor general cognitive impairment in late‐onset Pompe patients. These findings are in sharp contrast with the widespread WMA and cognitive problems found in some classic infantile patients.